The Territorial Transformation of Tampuk Pinang Pura Housing Complex in Pangkalpinang, Indonesia - Putra, Hadi Jaya; Pratiwi, Wiwik D.; Syafrina, Andina (Institute of Research and Community Services of Universitas Tanjungpura and Center of Southeast Asian Ethnicities, Cultures and Societies (Joint collaboration between Universitas Tanjungpura and National Taitung University), 2024)
Situated on Dealova Hill in Pangkalpinang City, the Tampuk Pinang Pura (TPP) territory has faced longstanding challenges associated with juvenile delinquency, encompassing issues such as drug abuse, illegal street racing, promiscuity, and alcohol consumption. Responding to these issues, the Pangkalpinang City Government initiated the construction of Dealova Park in early 2020, envisioning a Green Open Space (GOS) to counteract negative stigmas and foster a positive environment. Through a deductive-rationalistic qualitative study, this research explores the transformation of TPP territory, emphasizing the pivotal role of the governing authority in this process. The research illuminates that successful development necessitates meticulous consideration and the effective utilization of crucial public infrastructure elements such as electricity, water, drainage, and public circulation. The introduction of Taman Dealova signifies not only a physical transformation but also a paradigm shift in governance practices, highlighting the influential role of the city government in territorial changes. Beyond physical alterations, the study reveals the dynamic interplay between spatial development and governance, providing nuanced insights into urban spatial planning complexities and the transformative impact of governing bodies on spatial landscapes.